2005
DOI: 10.1161/circulationaha.105.565598
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Whole-Body Functional Rescue in Congestive Heart Failure and Muscular Dystrophy Hamsters by Systemic Gene Transfer

Abstract: Background-The success of muscular dystrophy gene therapy requires widespread and stable gene delivery with minimal invasiveness. Here, we investigated the therapeutic effect of systemic delivery of adeno-associated virus (AAV) vectors carrying human ␦-sarcoglycan (␦-SG) gene in TO-2 hamsters, a congestive heart failure and muscular dystrophy model with a ␦-SG gene mutation. Methods and Results-A single injection of double-stranded AAV serotype 8 vector carrying human ␦-SG gene without the need of any physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 46 publications
2
71
0
1
Order By: Relevance
“…26,27 Our own effort here also identified a hybrid muscle-specific synthetic promoter, in which a modified MCK enhancer was fused with an original synthetic muscle promoter (C5-12). 33 This 520 bp hybrid promoter (E-Syn) is 2-3 stronger than the original C5-12 promoter. The E-syn is active not only in the heart and diaphragm but also in other skeletal muscles without apparent myofiber-type preference, suitable for gene therapy intended for both muscle and heart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Our own effort here also identified a hybrid muscle-specific synthetic promoter, in which a modified MCK enhancer was fused with an original synthetic muscle promoter (C5-12). 33 This 520 bp hybrid promoter (E-Syn) is 2-3 stronger than the original C5-12 promoter. The E-syn is active not only in the heart and diaphragm but also in other skeletal muscles without apparent myofiber-type preference, suitable for gene therapy intended for both muscle and heart.…”
Section: Discussionmentioning
confidence: 99%
“…33 This promoter was active in both heart and skeletal muscles, including the diaphragm, throughout the body. However, we did not investigate if it also displays myofiber-type preference.…”
Section: Examination Of the Dmck Promoter In Transgenic Mice With Lacmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The efficient cardiac gene transfer in a model of dilated cardiomyopathy also emphasizes the therapeutic relevance of our approach, as it has been shown that AAV-mediated reconstitution of d-sarcoglycan AAV targeting Y Ying et al in d-sarcoglycan-deficient TO-2 hamsters can extend the lifespan of these animals by preventing heart failure. 50 Similar approaches for targeted gene transfer as described here may be used not only for therapeutic applications, but also for fundamental analysis of gene function in animal models.…”
Section: Transgene Expression In Murine Hearts Following Systemic Admmentioning
confidence: 99%
“…11 Cardiac expression of potentially therapeutic proteins through virally mediated gene transfer into the myocardium is a potential strategy for the treatment of heart disease. 12,13 Benefits of this approach over recurrent therapeutic interventions may include locally higher levels of protein expression, fewer systemic side effects and long-term myocardial expression of the desired protein when using vectors such as adeno-associated viruses (AAV). However, the potential adverse effects of the viral vector or the cardiac-expressed proteins that they encode remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%